UJI AKTIVITAS GEL TABIR SURYA EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) DENGAN VARIASI GELLING AGENT CARBOPOL 940 SECARA IN VITRO - Hikmah Dwi Rahmawati; Endang Sri Rejeki; Anita Nilawati (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
Excessive sun exposure is dangerous for humans because it has many detrimental effects on the eyes, immune system as well as on the skin. Sunscreen can prevent the harmful effects of UV radiation and free radicals. Flavonoid compounds in mangosteen rind have natural sunscreen activity. The purpose of this study was to determine the physical quality and stability and activity of the ethanol extract gel of mangosteen peel in vitro with variations of carbopol 940. The extract was obtained from the maceration process using 70% ethanol. The gel was formulated using 0.1% extract and 0.5% gelling agent variations; 1%; and 1.5%. Gel test parameters including organoleptic test, homogeneity, viscosity, pH, spreadability, adhesion stability test cycling test, and sunscreen gel activity test were carried out in vitro by measuring the value of Sun Protection Factor (SPF) using UV spectrophotometry. The results showed that the 0.1% mangosteen rind ethanol extract gel formulation with variations of the gelling agent carbopol 940 0.5;1 and 1.5% had good physical quality and stability as well as sunscreen activity with an SPF value of 41,099; 39,898; 39,270 with the ultra category.